Identifying Customer Expected Content and Structural Dimensions of Bank Advertising Slogans - Shahriar Azizi; Majid Hasaninejad; Amin Dini; Asyeh Omidian; Fatemeh Farhikhteh (تحقیقات بازار یابی نوین, 2012)
Advertising slogans are frontier in corporate campaigns. Privatizations, entrance of private banks and totally electronic banks have intensified bank competitions. Having effective advertising slogan is a way to attract banking customers in the new competitive climate. In this article, the most important components of a good slogan have been identified from customers’ viewpoint using Chomsky’s theory of transformational grammar; qualitative and exploratory approach; and interviewing with 70 customers. Findings indicate that the frequencies of content indexes are four times higher than structural dimension from customers’ point of view, while both of content and structural dimensions are supplementary and inseparable. In addition, the first five indexes of good advertising slogans are speed in providing services, appropriate treat to customer, shortness, and attention to security and trust.